“Obesidad infantil y autoestima en estudiantes de la Unidad Educativa “Miguel Ángel León Pontón”. Riobamba. marzo – julio 2017”. - Pallarozo Calba, María Verónica (2018)
The present investigation addressed the issue of Childhood Obesity and Self-esteem in students of the Educational Unit "Miguel Ángel León Pontón", realizing its importance in the development of both physical and emotional children, and at the same time affecting their social relationships among peers, the purpose was seen to analyze Childhood Obesity in relation to Self-esteem. Methodologically it is a non-experimental design research; of type of cross-sectional study; by the descriptive, correlational level. The population was composed of the students of the Educational Unit "Miguel Ángel León Pontón" and the sample was intentionally non-probabilistic, with 15 students of the fourth grade "A". The technique used in self-esteem is psychometric tests, whose instrument to measure the levels of it is the A-EP of Rodolfo Ramos with his questionnaire for the evaluation structured by 17 dichotomous questions and himself obesity was with the tables of the nutritional status for children, children and adolescents from 5 to 18 years of age, so it was used to determine BMI, respectively, based on age, gender, weight and height. After the analysis and interpretation of data it is concluded that there is a high prevalence of obesity with 46.7%, and at risk of overweight in 26.7%. The levels of self-esteem were higher score in a low self-esteem with 33.3% which indicates that there is a direct relationship between obesity and low self-esteem, with a significant relationship of moderate positive degree.